Behavior and Attention Problems in Eight-Year-Old Children with Prenatal Opiate and Poly-Substance Exposure: A Longitudinal Study. - Egil Nygaard; Kari Slinning; Vibeke Moe; Kristine B Walhovd (PLoS ONE, 2016)
Multiple studies have found that children born to mothers with opioid or poly-substance use during pregnancy have more behavior and attention problems and lower cognitive functioning than non-exposed children. The present study aimed to investigate whether behavior and attention problems are more prominent than general cognitive deficits in this risk group and whether the problems wane or increase over time. This prospective longitudinal cross-informant study compared 72 children who were prenatally exposed to heroin and multiple drugs with a group of 58 children without known prenatal risk factors. Group differences in caregivers' and teachers' reports of the children's behavior and attention problems based on the Child Behavior Check List and the ADHD Rating Scale were compared based on group differences in general cognitive functioning at 4 ½ and 8 ½ years of age. Both parent and teacher reports suggest that the exposed group has significantly more problems in several behavioral areas than the comparison group, particularly with regard to attention problems. The preschool teachers had already reported these problems when the children were 4 ½ years old, whereas the caregivers reported these problems mainly when the children were 8 ½ years old. The group differences in behavioral and attentional problems were not significantly greater and some were even significantly smaller than the group differences in general cognitive abilities. These findings suggest that children subject to prenatally drug exposure have increasing problems in multiple areas related to behavior from preschool age to 8 ½ years but that these problems do not seem to be specific; i.e., they are not more severe than the problems with general cognitive abilities found for this group.